Management Accountability of Zakat and Its Role to Empower Creative Economy - Tenriwaru; Musrifah Azzahra Said; Budiandriani (International Journal of Religious and Cultural Studies, 2022)
This study aims to determine the role of zakat funds in increasing the empowerment of the creative economy and applying accountability in the management of its financial statements. This qualitative study obtained data from its financial statements through direct interviews with the distribution and financial division of Badan Amil Zakat Nasional in Mamuju. The results of this study indicate that the empowerment of the creative economy at Badan Amil Zakat Nasional in Mamuju in the form of business capital has a positive impact on mustahik in improving their standard of living and accountability is needed by Badan Amil Zakat Nasional as a form of accountability to zakat stakeholders.